2011
DOI: 10.1002/cbf.1837
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidants in patients receiving total parenteral nutrition after gastrointestinal cancer surgery

Abstract: Total parenteral nutrition (TPN) is essential for patients with postoperative impairing gastrointestinal function who are unable to receive and absorb oral/enteral feeding for at least 7 days. Oxidative stress plays a major role in the ethiopathogenesis of cancers. In this study, total antioxidant status (TAS), glutathione peroxidase (GPx), superoxide dismutase, malondialdehyde and ascorbic acid were studied in patients operated because of small intestine, colorectal or pancreatic cancer and subsequently recei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 30 publications
(57 reference statements)
0
6
0
Order By: Relevance
“…Although the pathogenesis of PI-IBS is not well understood, a large body of evidence suggests that oxidative stress and inflammation play a pivotal role in the occurrence and persistence of its symptoms ( Akiho et al, 2010 ; Kaji et al, 2016 ). The imbalance of reactive oxygen species and antioxidant enzymes as well as the imbalance of proinflammatory cytokines and anti-inflammatory cytokines play a key role in the development of PI-IBS ( Szpetnar et al, 2012 ; Sundin et al, 2015 ). Consistent with these findings, we found that the levels of biomarkers of oxidative stress (4-HNE, protein carbonyl, and 8-OHdG), the expression of proinflammatory cytokines (TNF-α, IL-6, IL-17, and ICAM-1), and the activity of NF-κB were remarkably increased in the serum and colon of Trichinella spiralis -infected mice as well as LPS-treated NCM460 colonic cells.…”
Section: Discussionmentioning
confidence: 99%
“…Although the pathogenesis of PI-IBS is not well understood, a large body of evidence suggests that oxidative stress and inflammation play a pivotal role in the occurrence and persistence of its symptoms ( Akiho et al, 2010 ; Kaji et al, 2016 ). The imbalance of reactive oxygen species and antioxidant enzymes as well as the imbalance of proinflammatory cytokines and anti-inflammatory cytokines play a key role in the development of PI-IBS ( Szpetnar et al, 2012 ; Sundin et al, 2015 ). Consistent with these findings, we found that the levels of biomarkers of oxidative stress (4-HNE, protein carbonyl, and 8-OHdG), the expression of proinflammatory cytokines (TNF-α, IL-6, IL-17, and ICAM-1), and the activity of NF-κB were remarkably increased in the serum and colon of Trichinella spiralis -infected mice as well as LPS-treated NCM460 colonic cells.…”
Section: Discussionmentioning
confidence: 99%
“…TPN administration can also cause a reactive oxygen species to be produced, and these peroxide contaminations could induce oxidative stress, leading to cell death [ 48 , 49 ]. Wesley et al .…”
Section: Discussionmentioning
confidence: 99%
“…The administration of postoperative total parenteral nutrition has been found to decrease the rate of further complications, improve antioxidant capacity, and improve nitrogen balance in cancer patients postoperatively. 37,38 Patients who received essential branched-chain amino acid support of leucine, isoleucine, and valine via total parenteral nutrition postoperatively were found to have an improved or more positive nitrogen balance despite the stress-induced catabolic state after surgery. 37 Furthermore, total parenteral nutrition administered in the postoperative period has been shown to alleviate oxidative stress ensuing from gastrointestinal surgery.…”
Section: Total Parenteral Nutritionmentioning
confidence: 99%